STUDI META-ANALISIS: KREDIT USAHA TANI DAN KESEJAHTERAAN PETANI (Universitas 17 Agustus 1945 Surabaya, 2022)
This study aims to determine the extent to which the influence of credit to improve farmers' welfare. This study uses a meta-analysis approach from international and national journals published from 2018 to 2021. The results of several journal articles show that credit is very helpful in the agricultural process and can improve welfare for farmers, especially for farmers. Family Family, this is because by getting credit farmers will be able to carry out their agricultural business to improve agricultural yields which means it also increases income. With credit given by farmers, both from cooperatives and formal banking institutions, can also prevent farmers from getting credit or loans from non-formal credit institutions. On the other hand, the role of banking institutions greatly affects farmers in obtaining and obtaining credit for their agricultural capital.